Rationally tuning host–guest interactions to free hydroxide ions within intertrimerically cuprophilic metal–organic frameworks for high OH− conductivity. Issue 17 (10th March 2017) - Li, Ziyin; Zhang, Zhangjing; Ye, Yingxiang; Cai, Kaicong; Du, Fenfen; Zeng, Heng; Tao, Jin; Lin, Quanjie; Zheng, Ying; Xiang, Shengchang
Abstract : Rationally tuning host–guest interactions to free hydroxide ions within intertrimerically cuprophilic MOF for high OH − conductivity. Abstract : Hydroxide-anion-exchange membrane fuel cells (HEMFCs) are now considered as one of the most promising green energy-conversion technologies for stationary and mobile applications, showing high fuel conversion efficiency at high pH and low cost due to their ability to operate under basic conditions using non-precious metal catalysts. But one key impediment to commercialization is insufficient hydroxide ion (OH − ) conductivity of the central HEM component. Here, we report the development of free OH − anion-containing metal–organic frameworks (FOMOFs) with rationally tunable host–guest interactions for HEMs with high OH − conductivity. Among three solids obtained by post-synthesis treatment of ultrastable MOFFJU-66 with various bases, free OH − anions are observed inFJU-66·[EVIm]OH with strong host–guest interactions between the MOF backbone and guest cations. Despite the lowest OH − concentration, FJU-66·[EVIm]OH exhibits the highest OH − conductivity close to 0.1 S cm −1 . The high OH − conductivity achieved suggests the potential application of the FOMOFs for practical HEMs of fuel cells.